The effects of symbol format and symbol placement on identification accuracy and activation time. - Brock, Kris L.; Jenkins, Haley; Dukhovny, Elena (AAC: Augmentative & Alternative Communication, 2026)
The aim of this study was to determine whether animation improved symbol identification accuracy and activation time in consistent and variable grids. A 2 x 2 counterbalanced factorial design was used to determine the effects of symbol format (animated and static) and placement (variable and consistent) on identification accuracy, averaged activation time (s), and activation time change (s) from trial one to trial four in 42, 18- to 58-year-old adults without disabilities. A repeated measures ANOVA was conducted, and analyses revealed significant main effects for symbol format and placement and a significant interaction. Animated symbols were identified with greater accuracy than static symbols, while static symbols were selected on average.26 s faster than animated symbols. However, animated symbols in the consistent placement condition had greater identification accuracy and faster activation time by the 4th trial compared to all other conditions. The synergistic effects of animation and consistent symbol placement suggest that speech-language pathologists should use these features as tools to facilitate speed and accuracy of word production on speech-generating devices.